The Effect of Lycii Radicis Cortex Extract on Bone Formation in Vitro and in Vivo - Eunkuk Park; Hyun-Seok Jin; Doo-Yeoun Cho; Jeonghyun Kim; Mun-Chang Kim; Chun Whan Choi; Yilan Jin; Ji-Won Lee; Jin-Hyok Park; Yoon-Sok Chung; Dam Huh; Seon-Yong Jeong (Molecules, 2014)
Osteoporosis is a common skeletal disease caused by decreased bone mass; it enhances the risk of bone fracture. This study aimed to discover novel herbal extract(s) for the treatment of osteoporosis. We screened 64 ethanol extracts of edible plants native to Korea for their ability to increase the cellular proliferation and differentiation of two osteoblastic cell lines: C3H10T1/2 and MC3T3-E1. We selected a Lycii Radicis Cortex (LRC), Lycium Chinese root bark as the primary candidate. Treatment with LRC extract showed enhanced alkaline phosphatase activity and increased expression of bone metabolic markers Alpl, Runx2, and Bglap genes in both osteoblastic cell lines. There was no effect on the osteoclastic differentiation of primary-cultured monocytes from the mouse bone marrows. Furthermore, the study examined the effect of LRC extract in vivo in ovariectomizd (OVX) mice for 8 weeks and 16 weeks, respectively. Bone mineral density (BMD) was significantly higher in LRC extract-administered group than in the non-LRC-administered OVX control group. The results indicated that LRC extract prevented the OVX-induced BMD loss in mice via promoting the differentiation of osteoblast linage cells. These results suggest that LRC extract may be a good natural herbal medicine candidate for the treatment of osteoporosis.